Iron bacteria occurrence, problems and control methods in waters wells - Hackett, Glen | Lehr, PhD, Jay H. (Estados Unidos | ESTADOS UNIDOS National Water Well Association / Washington, 1985)
Contents: Classification and occurrence; Iron bacteria related problem; Control of iron bacteria
Sin Especificar
Fotocopia
Keywords: Bacterias-Coliformes fecales